Redesign of Railroad Stairs Using a Multi-Layer Quality Function Deployment Approach: Redesign Tangga Kereta Api Dengan Menggunakan Pendekatan Multi-Layer Quality Function Deployment - Karningsih, Putu; Kusumawardani, Citra (Universitas Muhammadiyah Sidoarjo, 2022)
Railway is one of the popular modes of public transportation in Indonesia, but there are conditions where length of platform does not cover the entire length of the railway coach. This causes access in and out passengers must be added with tools such as staircase. The condition of staircase that is currently available is large and heavy, so to place the staircase right at the door of the railway coach takes a longer time. The initial survey conducted on 106 passengers obtained data 34% of respondents stated that the staircase currently available are less comfortable to use, in addition 32.1% of respondents stated that the available staircases are not adequate in terms of number and physical condition. Based on this background, the study aims to redesign the staircase that according to the needs of two user they are: train passengers and Indonesian Train Service Provider by using the multi-layer Quality Function Deployment. The result of this study shows that both users agree that the design of new stair design should consider anthropometry of passengers, safety features, easy to be move during use (portable and light weight).